Teatment of Girolando cattle dermatophilosis using a combination of different plant extracts in the municipality of Abomey-Calavi, Republic of Benin - ADOLIGBE, CAMUS (My University, 2021)
Background and Aim: Dermatophilosis is a bacterial infection of the skin of animals. It is prevalent worldwide and is caused by Dermatophilus congolensis.  The study aimed to assess the therapeutic efficacy of different mixtures prepared with indigenous phytogenetic extracts from Benin in the management and treatment of Girolando cattle that showed high sensitivity to the disease compared to any other known cattle breed in Benin. Materials and Methods: Consequently,  two types of extract mixtures (extract mixture 1=Elaeis guineensis kernel oil + essential oil of Ocimum gratissimum + sap of Jatropha multifidi; extract mixture 2= O. gratissimum + sap extract of J. multifida) of 20% concentration were prepared and tested on eight Girolando cattle. Two different parts of the affected skin with acute lesions of dermatophilosis were debrided, and 0.5 mL of each of the extract mixture was applied per square centimeter of a single zone of the affected skin. Results: Both extracts mixtures were found to possess significant wound healing properties compared to the control (procaine G penicillin). However, the extract mixture 1, which was made up of Elaeis guineensis kernel oil, essential oil of O. gratissimum and sap of J. multifida (Linn), showed a better result. This was evident by increase in the rate of wound contraction and healing without recurrence 2 weeks after the end of the experiment and the subsequent immediate manifestation of hair or hair growth at the affected area. Conclusion:  The preliminary findings of this study are very promising. Extract mixture 1 could serve as an alternative in the treatment or management of bovine dermatophilosis in Benin and other dermatophilosis endemic areas of the world. However, in vitro testing and sensitivity against isolated D. congolensis organism using extract mixture 1 as well as cost implications should be studied.
Keywords: farmer resilience; indigenous plants; plant extract; sustainable cattle breeding